Antifungal activity of Flavonoids and Tannins Extracted from Geranium lucidum L against some pathogenic fungi - Mostafa Q. Mostafa; Talib O.H. Al-Khesraji; Sirwan H. Salih (Tikrit Journal of Pure Science)
The present study aimed to identify the effectiveness of anti-fungal extracts Aqueous[hot and cold water]  and alcoholic (ethanolic and Methanolic) plant Geranium lucidum developing northern Iraq on four types innate nurse (Microsprum canis, Trichophyton mentagrophytes, Pencillium chrysogenum and Fusarium oxysporeum) and the content Tannins content and Flavonoids content using HPLC technique, and aimed to draw Glycoside content and Tannin content and test its effectiveness against fungi aforementioned and compared it by extracts, The results showed that the studied plant contained all the active compounds that were detected. The effectiveness of all studied extracts against the tested fungi showed that the water extract (hot at an average of 11.19 mm and cold with an average of 10.27 mm) and the methanol extract at an average of 10.66 mm were the most effective compared to the negative control and the rest of the extracts, The results showed that T.mentagrophytes with an average of 12.11 mm and F.oxysporeum with an average of 11.48 mm were the most affected by plant extracts compared to other tested fungi .